Sickle Cell Disease - Erhabor, Osaro (IntechOpen, 2022)
This book presents a comprehensive overview of sickle cell anemia, with chapters addressing diagnosis and clinical, psychosocial, and pharmacological management of patients with this disease. It is a vital resource for biomedical science and medical students, interns, pediatricians, general physicians, and other healthcare professionals involved in offering care and support to patients with sickle cell disease.